Distribution and Relationship of Radionuclides and Heavy Metal Concentrations in Marine Sediments from the Areas Surrounding the Daya Bay Power Plant, Southeast China - Chengpeng Huang; Yunpeng Lin; Haidong Li; Binxin Zheng; Xueqiang Zhu; Yiming Xu; Heshan Lin; Qiangqiang Zhong; Fangfang Shu; Mingjiang Cai; Yunhai Li (Journal of Marine Science and Engineering)
Radionuclides and heavy metals pose potential risks to marine ecosystems and human health. Daya Bay, the site of China’s first commercial nuclear power plant, has experienced significant anthropogenic impacts, yet the extent of radionuclide and heavy metal contamination remains unclear. Nineteen surface sediment samples were collected in January 2024 and analyzed for natural (210Pb, 228Th, 226Ra, 228Ra, and 40K) and anthropogenic (137Cs) radionuclides, heavy metals (Cu, Pb, Zn, Cd, Cr, Mn, Hg, and As), grain size, and total organic carbon (TOC). The surface sediments of Daya Bay were predominantly fine-grained, with TOC levels ranging from 0.41% to 1.83%, influenced significantly by riverine input from the Dan’ao River. Natural radionuclides exhibited distinct spatial patterns: 210Pb and 228Th activity levels were higher in fine-grained sediments, and correlated with TOC, indicating adsorption and sedimentation controls. In contrast, anthropogenic 137Cs activity was low and showed no significant impact from the nuclear power plant. Notably, the absence in the samples of key anthropogenic radionuclides typically associated with nuclear power plant operations further confirmed the negligible impact of the power plant on local sediment contamination. The results indicated that the baseline levels of both natural and anthropogenic radionuclides and heavy metals were predominantly influenced by natural processes and local anthropogenic activities rather than the operation of the nuclear power plant. This study establishes critical baselines for radioactivity and heavy metals in Daya Bay, underscoring effective pollution control measures and the resilience of local ecosystems despite anthropogenic pressures.